Estação Ecológica do Tripuí, Ouro Preto, MG: geologia e geomorfologia da área - Fernandes, Selma Maria; Fonseca, Marco Ântonia; Fonseca, Venina Velosa; Dami, José Donizeti (Sociedade & Natureza, 1991)
Estação Ecológica do Tripuí, Ouro Preto, MG: geologia e geomorfologia da área